Draft BS EN 62841-2-23 Ed.1.0. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Particular requirements for hand-held die grinders and small rotary tools (14th February 2022) - British Standards Institution,
No abstract available